Cysteine Cathepsins in Tumor-Associated Immune Cells - Jakoš, Tanja; Pišlar, Anja; Jewett, Anahid; Kos, Janko (Frontiers in Immunology, 2019)
Cysteine cathepsins are key regulators of the innate and adaptive arms of the immune system. Their expression, activity and subcellular localization are associated with the distinct development and differentiation stages of immune cells. They promote the activation of innate myeloid immune cells since they contribute to toll-like receptor signaling and to cytokine secretion. Furthermore, they control lysosomal biogenesis and autophagic flux, thus affecting innate immune cell survival and polarization. They also regulate bidirectional communication between the cell exterior and the cytoskeleton, thus influencing cell interactions, morphology and motility. Importantly, cysteine cathepsins contribute to the priming of adaptive immune cells by controlling antigen presentation and are involved in cytotoxic granule mediated killing in cytotoxic T lymphocytes and natural killer cells. Dysregulated proteolysis also contributes significantly to tumor progression by modulation of the antitumor immune response. Tumor-associated myeloid cells, such as tumor-associated macrophages and myeloid-derived suppressor cells, are known for their tumor promoting and immunosuppressive functions, and constitute the major source of cysteine cathepsin activity in cancer.